2015
DOI: 10.21829/azm.2015.312985
|View full text |Cite
|
Sign up to set email alerts
|

Preferencias entre cinco carbohidratos en Pheidole bilimeki (Hymenoptera: Formicidae)

Abstract: , J. V. 2015. Preferencias entre cinco carbohidratos en Pheidole bilimeki (Hymenoptera: Formicidae). Acta Zoológica Mexicana (n. s.), 31(2): 291-297. RESUMEN.Los carbohidratos comunes en fuentes naturales de energía para las hormigas son: sacarosa, fructosa, glucosa, trehalosa y melezitosa. En este estudio se establecieron preferencias entre estos cinco carbohidratos en Pheidole bilimeki Mayr a través de la conducta de reclutamiento. El orden de efectividad reclutadora de los cinco quí-micos fue: sacarosa > me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The quality and concentration of nutrients may affect the number of ovarioles and, as a consequence, cause changes in vitellogenesis, maturation, and egg production by insects (Engelmann, 1970). Carbohydrates, proteins, and lipids are associated with the production of enzymes and hormones in the vitellogenesis process (Rosas‐Mejía et al., 2015). Our results show that females previously fed on banana presented a profile of nutrient levels, reproduction, and appearance of oocytes similar to females fed only on cotton squares.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and concentration of nutrients may affect the number of ovarioles and, as a consequence, cause changes in vitellogenesis, maturation, and egg production by insects (Engelmann, 1970). Carbohydrates, proteins, and lipids are associated with the production of enzymes and hormones in the vitellogenesis process (Rosas‐Mejía et al., 2015). Our results show that females previously fed on banana presented a profile of nutrient levels, reproduction, and appearance of oocytes similar to females fed only on cotton squares.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible cellular effect caused by insecticides is histopathological changes. In the gonads, such effects may result from the direct action of the xenobiotic on the target organ and/or from alterations in nutritional acquisition, which may lead to a reduction in gamete formation and consequent population reduction (Rosas-Mejía et al, 2015;Cruz et al, 2017;Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, little research has been carried out on the urban myrmeco fauna of Mexico. One study detailed a rapid descriptive ecological assessment for testing the effect of urbanization on ant morphospecies (MacGregor-Fors et al, 2015), and several additional studies have reported on the importance of urban green spaces as reservoirs of ant diversity (Rocha & Castaño-Meneses, 2015), the bait preferences of ants (Rosas-Mejía et al, 2015), and new species records (Rosas-Mejía et al, 2013;Landero-Torres et al, 2014). However, it is crucial to contribute toward current knowledge of the real influence of urbanization on ant species diversity at a local and landscape level.…”
Section: Research Article -Antsmentioning
confidence: 99%